PEMODELAN SISTEM INFORMASI PENLOK 108 (DI KANDATEL BANDUNG) MENGGUNAKAN JARINGAN SYARAF TIRUAN - DARMAWAN, BUDI
One of service offered by PT Telkom to its customers is information of other customers\' phone number, called 108 local information system. In this system, the traffic distribution of customers\' incoming call are processed. This is known as queue system problem. Service facility in this 108 local information system is the availability of agent/operator and buffer that can sustain every customer calling for service. The supply of agent and buffer depends on the size of traffic, such that each customer can be well-served. Therefore, a regulation to determine a queue system\'s capacity, the number of agents and buffers, are needed to reach a satisfactory service level. This service level is determined by performance index consisting of parameters, as the number of missed call and the length of waiting time. In this research, a regulation was conducted on one of service facilities, namely agent capacity which had to be installed to serve a number of incoming calls. The agent regulation method used here was by approaching current queue system pattern, i.e. by using the artificial neural network. This research is looking for the models of queue system, number of agent regulation, and incoming-call prediction. Using these number of agent from the systems model , an increase in call productivity was added as much as 12,18 % foe model 1 and 18,71 % for model 2. In addition, there are a decrease in the length of waiting time as much as 26,42 % for model I and 73,43 % for model 2.